Sustainable Intensification Farming as an Enabler for Farm Eco-Efficiency? - Meike Weltin; Silke Hüttel (Environmental and Resource Economics, 2022)
Sustainable Intensification (SI) practices offer adopters exploiting improvement potentials in environmental performance of farming, i.e. enhance ecosystem functionality, while maintaining productivity. This paper proposes a directional meta-frontier approach for measuring farms' eco-efficiency and respective improvement potentials in the direction of farms' ecological output for SI evaluation. We account for farms' selection processes into SI using a behavioural model and rely on a matched sample for adopters and non-adopters of agronomic SI practices from the northern German Plain. We conclude that the SI adopters determined the sample's system frontier and showed higher mean eco-efficiency, but that most farms in our sample did not fully exploit the improvement potentials in biodiversity as ecological outcome.
Keywords: Q12; Q15; Q57; 330; Sustainable intensification concept; Directional data envelopment analysis; Eco-efficiency; Environmental sustainability; Matching; Meta-frontier